Rapid colistin susceptibility determination by a novel fluorogenic method in Klebsiella pneumoniae strains - Negin, Meliha; Ayas, Meltem; Akyar, Isin; Mozioglu, Erkan; Kocagoz, Tanil (Frontiers in Microbiology, 2026)
IntroductionKlebsiella pneumoniae is a causative agent that can lead to fatal infections, especially in intensive care patients. Colistin treatment is employed as a last resort in K. pneumoniae infections caused by strains resistant to almost all antibiotics from different groups. However, in recent years, colistin resistance has also become widespread in K. pneumoniae strains. Therefore, before starting treatment with this relatively toxic drug, it is essential to know its susceptibility to colistin. A standard colistin susceptibility test typically takes 24–48 h. In this study, we investigated the accuracy of our novel fluorometric method, which enables the determination of colistin minimal inhibitory concentration (MIC) within 2 h for K. pneumoniae.MethodsFor this purpose, we determined and compared the MIC values of 24 colistin-resistant and 18 colistin-susceptible K. pneumoniae strains using the standard broth microdilution method and the new fluorometric method.ResultsIn the comparison of MIC values determined by standard and fluorometric methods, it was observed that the MIC values of 22 strains were identical, there was a 1-dilution (1/2) difference in 14 strains, and a 2-dilution (1/4) difference in six strains.DiscussionWe believe that the new fluorometric antibiotic susceptibility testing method will be a valuable tool in the rapid detection of colistin resistance in K. pneumoniae and thus for guiding appropriate treatment in critically ill patients.